Rody w Pacholęciu hetmańskim Wincentego Pola - Bryła, Władysława (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author provides information about the writer and presents the narrative poem Pacholę hetmańskie, which is further analysed. The main focus of the presentation is the Tarnowski family and the hetman Jan Tarnowski who lived in the 16th century. The Bobol, Odrowąż and Rożanka families are also mentioned, with the last one being the poem’s narrator. The members of all these families are characterised by patriotism, Catholicism, wisdom and warm-heartedness towards other people. Pol presented an idealized picture of the Polish nobility of the 16th century.